Psychometric Properties of Hindi Version of Physical Activity Recall Assessment for People with Spinal Cord Injury (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: The most widely used type of physical activity measure is the self-report survey. Of the availableself-report physical activity measures, the vast majorities were developed for use in the general populationand typically focus on measuring participation in recreational and sport activities. As a result, the existingself-report measures are insufficiently sensitive to measure very low intensity activities that might accountfor the bulk of daily energy expenditure among people with SCI. The content of these measures also fails tocapture activities that are part of SCI lifestyle. ‘Physical Activity Recall Assessment for People with SpinalCord Injury’ [PARA-SCI] was published in August 2005. PARA-SCI is a measure of physical activity forindividuals with SCI who use a wheelchair as their primary mode of mobility. It has been translated invarious languages, thus the aim of the study is to study the psychometric properties of Hindi version ofphysical activity recall assessment-SCI.Methods: PARA SCI was translated in phase 1 of the study and the reliability and validity of the instrumentwas doneResults: There was significant correlation observed in test –retest reliability and Vo2 max calculated by 12minute wheelchair test correlated with the subcomponent of PARA SCIConclusion: The Hindi version of PARA-SCI is a reliable and valid instrument